On domain adjectives and the metaphors they modif - Zwarts, Joost (Proceedings of the Amsterdam Colloquium, 2019)
The metaphorical meaning of a noun like storm is modeled as a function from domains to kinds of storms. The argument of this function can be set by a domain adjective (e.g., a political storm), but also adverbially or contextually. By making explicit how domain specification works, this proposal not only brings conceptual domains and metaphors into the heart of formal semantics, but it also opens avenues towards an account of non-metaphorical domain modifiers more generally (e.g., botanical fruit).